Analisis Pengaruh Variasi Panjang Header Knalpot terhadap Performa Motor Manual 100cc dengan Metode Kruskal-Wallis: Analysis of the Effect of Exhaust Header Length Variations on the Performance of a 100cc Manual Motorcycle with Kruskal-Wallis Method - Jhony Langgeng Baruna Wirawan; I Wayan Purnayasa (Jurnal Pendidikan Teknik Mesin Undiksha, 2025)
This study investigates the effect of varying exhaust header length on the engine performance of a 100cc manual motorcycle using a non-parametric statistical approach. Three header lengths (30 cm, 45 cm, and 60 cm) were evaluated. Performance indicators assessed included torque, power (horsepower), and specific fuel consumption (SFC), measured at five engine speed settings: 3000, 3500, 4000, 4500, and 5000 rpm. Torque and power measurements were performed using a dynamometer (dynotest), while fuel consumption was recorded using a flowmeter. For data analysis, the Kruskal–Wallis test was applied, as preliminary Shapiro–Wilk and Levene tests indicated that the dataset did not meet the assumption of normality. Statistical results indicate that exhaust header length has a significant effect on torque and fuel consumption at all tested rpm levels. Power output also exhibits significant variation, especially at medium to high engine speeds. Among the configurations tested, the 45 cm header consistently delivered the best overall performance, producing the highest torque and power while achieving the most efficient fuel consumption. These findings highlight the critical role of optimal exhaust header design in maximizing the efficiency and performance of small-displacement motorcycle engines.